Attitudes of the German public to restrictions on persons with mental illness in 1993 and 2011. (4th April 2014) - Angermeyer, M. C.; Matschinger, H.; Schomerus, G.
Abstract : Aims: In recent years, the United Nations Convention on the Rights of Persons with Disabilities, the Mental Health Declaration for Europe and other initiatives laid the ground for improving the rights of persons with mental illness. This study aims to explore to what extent these achievements are reflected in changes of public attitudes towards restrictions on mentally ill people. Methods: Data from two population surveys that have been conducted in the 'new' States of Germany in 1993 and 2011 are compared with each other. Results: The proportion of respondents accepting compulsory admission of mentally ill persons to a psychiatric hospital remained unchanged in general, but the proportion opposing compulsory admission on grounds not sanctioned by law declined. In contrast, more respondents were opposed to permanently revoking the driver's license and fewer supported abortion and (voluntary) sterilisation in 2011. Concerning the right to vote and compulsory sterilisation, the proportion of those who did not give their views increased most. Conclusions: Two divergent trends in public attitudes towards restrictions on people with mental disorders emerge: While, in general, people's views on patients' rights have become more liberal, the public is also more inclined to restricting patients' freedom in case of deviant behaviour.